Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1890/12-0272.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial fidelity of skeletal remains: elk wintering and calving grounds revealed by bones on the Yellowstone landscape

Abstract: Abstract. The spatial distributions of bones on landscape surfaces (death assemblages) may contain high-quality data on species' landscape use. Previous investigations into the spatial fidelity of death assemblages focused on general habitat preferences of the source community. Using well-studied elk populations of Yellowstone National Park, I test the geographic sensitivity of death assemblages by assessing the fidelity of shed elk antlers to the distribution of bull elk in late winter (documented through aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Compared with the Yellowstone bone assemblage, the ANWR calving ground shows significantly higher relative abundances of neonatal MNI (Mann-Whitney U ¼ 128: p ¼ 0.021, one-tailed, figure 3b; electronic supplementary material, appendix C). While neonatal remains in Yellowstone are also faithful to known elk calving grounds [15], even localities with the highest relative abundances of neonatal MNI are below the median concentration of neonates in ANWR. Sample-size standardizing the Yellowstone plots further accentuates these differences (figure 3b, 'Yellowstone sample stand.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Compared with the Yellowstone bone assemblage, the ANWR calving ground shows significantly higher relative abundances of neonatal MNI (Mann-Whitney U ¼ 128: p ¼ 0.021, one-tailed, figure 3b; electronic supplementary material, appendix C). While neonatal remains in Yellowstone are also faithful to known elk calving grounds [15], even localities with the highest relative abundances of neonatal MNI are below the median concentration of neonates in ANWR. Sample-size standardizing the Yellowstone plots further accentuates these differences (figure 3b, 'Yellowstone sample stand.…”
Section: Resultsmentioning
confidence: 95%
“…Interestingly, the Yellowstone plots closest to the maximum ANWR female antler concentration are from localities that are heavily used by bull elk during the late-winter period of maximum antler shedding [15]. Sample-size standardizing the Yellowstone plots to those of ANWR accentuates differences between the two localities (figure 3a, 'Yellowstone sample stand.').…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although hunting activity could be particularly important when analyzing band recovery data at small spatial scales (i.e., at the county-or even state-scale; Calenge et al 2010), we suggest that their impacts may be dampened at flyway-scale analyses across multiple decades. Thus, at the broad spatial and temporal scales analyzed here, although hunter preferences or behaviors may change over time within a county, state, or even region, much of this high-frequency variability, and that associated with stochastic climatic events and population fluctuations, should be effectively averaged out (as observed in other studies of multi-decadal data; Western and Behrensmeyer 2009, Miller 2011, Behrensmeyer and Miller 2012, Miller 2012). This does not suggest that our analyses are free of bias (including hunter bias), but that our scale of analysis should limit some of their effects.…”
Section: Banding Data Biasesmentioning
confidence: 98%
“…Determining how much of the biological signal reaches shell beds after the influence of biological and physical agents and time averaging, and how this preservability varies in time and space, remains one of the key steps in paleontological analysis (Fürsich 1978(Fürsich , 1995Kidwell 1985Kidwell , 1986Kidwell , 2001Kidwell et al 1986; Fü rsich and Aberhan 1990; Kidwell and Flessa 1995;Kowalewski et al 2003;Tomašových et al 2006). Previous contributions have found that there is fairly good agreement between the species composition of living assemblages (LAs) and the co-occurring death assemblages (DAs) in marine environments (e.g., Fü rsich and Flessa 1987; Kidwell 2001Kidwell , 2002Kidwell , 2013; see examples in Kidwell and Bosence 1991) as well as in other settings and/or taxa, such as land snails (Yanes et al 2008;Yanes 2011), fresh water mollusks (De Francesco et al 2013;Erthal et al 2011;Tietze and De Francesco 2012), marine mammals (Liebig et al 2003), ungulate mammals (Miller 2011(Miller , 2012, nonvolant terrestrial mammals , and small mammals (Terry 2010; see other examples in Kidwell and Tomašových 2013). However, the degree of similarity between living communities and the corresponding dead remains shows a large variation (Kidwell 2001), particularly among marine benthic communities (Kidwell and Bosence 1991;Zuschin et al 2000;Zuschin and Oliver 2003;Albano and Sabelli 2011;Feser and Miller 2014).…”
Section: Introductionmentioning
confidence: 99%